The Development of Copper‐Catalyzed Aerobic Oxidative Coupling of H‐Tetrazoles with Boronic Acids and an Insight into the Reaction Mechanism. Issue 8 (21st January 2014) - Liu, Chao‐You; Li, Yu; Ding, Jin‐Ying; Dong, De‐Wen; Han, Fu‐She
Abstract The development of a highly efficient and practical protocol for the direct CN coupling of H‐tetrazole and boronic acid was presented. A careful and patient optimization of a variety of reaction parameters revealed that this conventionally challenge reaction could indeed proceed efficiently in a very simple system, that is, just by stirring the tetrazoles and boronic acids under oxygen in the presence of different CuI or CuII salts with only 5 mol % loading in DMSO at 100 °C. Most significantly, the reaction could proceed very smoothly in a regiospecific manner to afford the 2, 5‐disubstituted tetrazoles in high to excellent yields. A mechanistic study revealed that both tetrazole and DMSO are crucial for the generation of catalytically active copper species in the reaction process in addition to their role as reactant and solvent, respectively. It is demonstrated that in the reaction cycle, the CuI catalyst could be oxidized to CuII by oxygen to form a [CuT2D] complex (T=tetrazole anion; D=DMSO) through an oxidative copper amination reaction. The CuII complex thus formed was confirmed to be the real catalytically active copper species. Namely, the CuII complex disproportionates to aryl CuIII and CuI in the presence of boronic acid. Facile elimination of the CuIII species delivers the CN‐coupled product. The results presented herein not only provide a reliable and efficient protocol for the synthesis of 2, 5‐disubstituted tetrazoles, but most importantly, the mechanistic results would have broad implications for the de novo design and development of new methods for Cu‐catalyzed coupling reactions.